The health benefits and risks of growing-your-own produce in an urban environment - Stubberfield, Jonathan (2018)
The practice of gardening and growing-your-own (GYO) produce in urban areas, has been associated with many potential benefits to health from increased fruit and vegetable consumption and exercise, but also health risks arising from exposure to potentially toxic elements (such as cadmium: Cd, and lead: Pb) in urban soils. However, the potential health benefits of gardening are currently overlooked by authorities during assessments of contaminated land, which may result in access to urban gardens and allotments being incorrectly restricted or removed because of concerns over the impact to human health. The trade-off between health benefits and risks is investigated in this thesis through: the sampling and analysis of the properties of allotment soils (chapter 2); a comparison of plant uptake models (chapter 3) verified using a pot experiment (chapter 4), and a questionnaire survey investigating the effect of gardeners’ routines on benefits and risks (chapter 5). The different areas of study are combined in the creation of a model framework developed to estimate health benefits and risks attributable to urban gardening (chapter 6).